[SPS seminar. Clinical psychology and disability] - The disability support assistant at school: the clinical psychological competence to think about relationship as an alternative to control and tolerance. - Giuliano, Sonia; Sarubbo, Maria (Rivista di Psicologia Clinica, 2013)
Recent legislative changes on the integration of disability in school seem to invite us to rethink the models that drive this area of intervention, in which many young psychologists are employed as assistant or culture educational specialist assistant. In this article, through the report of a specialist intervention care within a higher education institution, we wonder about the contribution that clinical psychology can make to develop this service. We compare models that include disability relying on the control and tolerance and models for context development. In the first ones diversity is not recognized as a resource, it must be adapted to the context and you will see, through the reported experience, as this model organizes the demand of intervention and, at the same time, imposes a very high cost within the school organization, making difficult to design future. The second one is the prospective adopted by the psychologists who make this intervention; within this model the client of the intervention is the school context and its competence to dealing with diversity: the function of the disability assistant is to become no longer necessary. How? Through a series of interpretative action able to establish on the organization the competence to think the relationships.